Political performances : theory and practice - Haedicke, Susan C. (Themes in theatre, 2009)
Political Performances: Theory and Practice emerges from the work of the Political Performances Working Group of the International Federation for Theatre Research/Fédération Internationale pour la Recherche de Théâtrale. The collection of essays strives to interrogate definitions and expand boundaries of political performance.